Textual Trappings in Emily Dickinson’s Selected Poems - Abdul Ameer, Sahar (Opción)
Dickinson´s poetry is unique for several reasons. For her poems can be regarded very private .She was interested in the innermost world of the human mind. Thus one of the foremost aspects of her poetry is the ability to condense a great theme or an intense involvement into a few lines. Both the structure as well as poetic diction of Dickinson were exceptionally inventive in her lifetime. She highlighted her poetry by a distinctive use of capitalization, and of punctuations she used primarily dashes. Such use was so innovative and helpful to the poet to interpret her intention. It also functions as providing different interpretations to the poem leading the reader to have a very vivid and active role in these interpretations. This also might be due to her own personality as well as the sensitive attitudes she has towards issues in life and her desire to add ambiguity to her poems that are supposed to talk about her own experiences and the situations she lived in. Thus, Dickinson’s poetic novelty is due to the spiritual forces of the world around her. Such a thing led her to have an acceptance of life as it is and gave her a distinctive style among which is the use of dashes as well as the intended capitalization to reflect in a very distinctive and unique way her intention as well as her conviction about life and the world around her. A conviction that is more personal and more of hers as well.